IN VITRO EVALUATION OF THE RESISTANCE OF THREE DIFFERENT POST SYSTEMS AGAINST FUNCTIONAL FORCES - Mustafa Kocacıklı (Selcuk Dental Journal)
Background: In order to ensure sufficient resistance against functional forces for dentin, which is severely weakened by excessive material loss in single-root single-canal teeth with previous root canal treatment, maximum retention and resistance must be the target.